Comprehensive genotyping of Turkish women with hirsutism - Polat, S.; Karaburgu, S.; Ünlühizarcı, K.; Dündar, M.; Özkul, Y.; Arslan, Y. K.; Karaca, Z.; Kelestimur, F. (Journal of endocrinological investigation, 2019)
Introduction Hirsutism is a medical sign rather than a disease affects 5–8% of women of reproductive age. Hirsutism is associated with hyperandrogenemia in most patients excluding those with idiopathic hirsutism (IH). The most common cause of hirsutism is polycystic ovary syndrome (PCOS) followed by IH and idiopathic hyperandrogenemia (IHA); however, the clinical presentation of non-classical congenital adrenal hyperplasia (NCAH) in females is often indistinguishable from other hyperandrogenic disorders with common clinical signs such as hirsutism. Objective The primary aim of the study is to examine the physical properties of the three genes and to make a detailed comparison of the mutations with the clinical data to contribute the etiology of hirsutism. Subjects and Methods 122 women admitted to the Endocrinology Clinic at Erciyes University Hospital with hirsutism were enrolled in the study between 2013-2014. All the participants were clinically evaluated. Protein-encoding exons, exon-intron boundaries of CYP21A2 (including proximal promoter), CYP11B1 and HSD3B2 genes were analyzed via state-of-the-art genetic studies. Results DNA sequencing analyses revealed two homozygous and three compound heterozygous 21-hydroxylase deficient (21OHD) NCAH patients. Additionally, three novel CYP21A2 mutations (A89V, M187I and G491S) and two novel CYP11B1 mutations (V188I and G87A) were determined. The frequencies of heterozygous mutations in CYP21A2 (including promoter), CYP11B1 and HSD3B2 genes were determined as 26.5% (15% coding region, 11.5% promoter), 11.5% and 0%, respectively. Conclusion 21OHD-NCAH prevalence was determined to be ~4%. Unexpectedly, high heterozygous mutation rates were observed in CYP11B1 gene and CYP21A2 promoter region. CYP11B1 and HSD3B2 deficiencies were not prevalent in Turkish women with hirsutism despite the existence of higher heterozygous mutation rate in CYP11B1 .